2016
DOI: 10.1177/1362361316648469
|View full text |Cite
|
Sign up to set email alerts
|

Translation and cultural appropriateness of the Autism Diagnostic Observation Schedule-2 in Afrikaans

Abstract: Autism Diagnostic Observation Schedule-2 is the 'gold standard' autism spectrum disorder observational assessment, and it is increasingly used in South Africa. However, its use is limited to English speakers, as it has not been translated into the country's other 10 official languages. Moreover, the cultural appropriateness of this tool has not been explored in South Africa. The Autism Diagnostic Observation Schedule-2 was translated into Afrikaans and assessed for cultural appropriateness to the 'coloured' po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Following these adaptations, the authors reported excellent discriminative validity and acceptable levels of sensitivity and specificity. Two recent studies in South Africa have also examined and evaluated the cultural adaptability of ASD measures in their context [14, 15]. The study by Smith and colleagues evaluated the cultural appropriateness of the Autism Diagnostic Observation Schedule-2 (ADOS-2) [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following these adaptations, the authors reported excellent discriminative validity and acceptable levels of sensitivity and specificity. Two recent studies in South Africa have also examined and evaluated the cultural adaptability of ASD measures in their context [14, 15]. The study by Smith and colleagues evaluated the cultural appropriateness of the Autism Diagnostic Observation Schedule-2 (ADOS-2) [15].…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies in South Africa have also examined and evaluated the cultural adaptability of ASD measures in their context [14, 15]. The study by Smith and colleagues evaluated the cultural appropriateness of the Autism Diagnostic Observation Schedule-2 (ADOS-2) [15]. Participants were requested to evaluate the cultural appropriateness of the materials and procedures for administering the ADOS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers need to consider the cultural appropriateness, acceptability, and affordability of all screening and diagnostic tools and should evaluate the potential of introducing method bias when evaluating tools developed in high‐income settings in low‐income settings (e.g., language use, materials used, literacy levels, activities, expectations of the child). In some SSA settings, we may find that instruments can be used with high fidelity and validly with only minor modifications [Chambers et al, ; Smith, Malcolm‐Smith, & de Vries, ].…”
Section: Screening and Diagnosis Of Asdmentioning
confidence: 99%
“…No changes were made to ADOS/ADOS-2 administration procedures. Translation and cultural adaptation of instruments often build on the experience obtained through prior use in a population, and involve data collection and analytical procedures specific to validation (Smith et al 2016). …”
Section: Introductionmentioning
confidence: 99%